Battery

By adding ester-containing polymer particles and lithium bis(trifluoromethanesulfonyl)imide complexes to the lithium-ion battery separator, the heat resistance and adhesion of the separator are enhanced, solving the problem of thermal runaway of lithium-ion batteries under heavy impact and improving safety and cycle performance.

CN120955310APending Publication Date: 2025-11-14CHONGQING COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511113448.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-08
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

When subjected to impact from heavy objects, lithium-ion batteries are prone to thermal runaway due to deformation and short circuits, which can lead to fires and explosions. Existing technologies are unable to effectively improve their safety performance.

Method used

By introducing ester-containing first polymer particles and lithium bis(trifluoromethanesulfonyl)imide from the electrolyte into the battery separator, and controlling the particle size and electrolyte weight ratio, a complex with high heat resistance is formed, which enhances the adhesion and compressibility of the separator, blocks the contact between the positive and negative electrodes, and delays thermal runaway.

Benefits of technology

It improves the battery's pass rate under heavy impact, reduces the risk of short circuit, and ensures that the battery's performance at room temperature and low temperature is not affected when it is not subjected to impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120955310A_ABST
    Figure CN120955310A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a battery. The battery comprises a diaphragm, a positive plate and an electrolyte, the diaphragm comprises a carrier layer and a coating, the coating comprises first particles, the components of the first particles comprise an ester group-containing polymer, the electrolyte comprises lithium bis (trifluoromethanesulfonimide), and the battery meets the following relational expressions: 0.3 < = D1 < = 0.8, 0.1 < = A < = 15, 0.3 < = A / D1 < = 48, D1 is the average particle size of the first particles, the unit is [mu] m, and D is the average particle size of the second particles. A is the weight ratio of the lithium bis (trifluoromethanesulfonyl) imide in the electrolyte, and the unit is%. According to the battery disclosed by the invention, the binding power of an interface between the diaphragm and the pole piece is relatively strong, the interface stability is relatively high, and the heat resistance is relatively high, so that the diaphragm can still keep relatively high binding power and integrity when a heavy object is impacted, the heavy object impact passing rate of the battery can be improved, and meanwhile, the diaphragm also can keep relatively good dynamic performance; and the low-temperature cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically to a battery. Background Technology

[0002] Lithium-ion batteries possess numerous advantages, including high energy density, long lifespan, and low self-discharge rate, and are currently used in various applications. During use, lithium-ion batteries can be subjected to external impacts or compression, causing internal deformation or even rupture, releasing a large amount of heat, and in severe cases, leading to fire or explosion. For example, during a heavy impact, the area of ​​a lithium-ion battery subjected to compression can instantly shatter, causing numerous short circuits between the positive and negative electrodes, releasing a significant amount of heat. Simultaneously, if the cell breaks into two parts, numerous burrs will form at the break point, piercing the separator and causing contact between the positive and negative electrodes, further exacerbating the short circuit. This internal short circuit, releasing a large amount of heat in a short time, is one of the causes of lithium-ion battery fires and explosions. Summary of the Invention

[0003] To overcome the problem of reduced safety performance of batteries under heavy impact in existing technologies, this invention provides a battery. When subjected to heavy impact, the battery of this invention can delay the thermal runaway trigger point, improve the battery's impact resistance rate, and simultaneously maintain high adhesion and integrity of the separator, preventing separator damage and displacement, further improving the battery's impact resistance rate. Furthermore, it does not affect the battery's room temperature and low temperature cycling performance when no heavy impact occurs.

[0004] To achieve the above objectives, the present invention provides a battery comprising a separator, a positive electrode, and an electrolyte. The separator comprises a carrier layer and a coating on one or both surfaces of the carrier layer. The coating comprises first particles, the first particles comprising a first polymer, the first polymer being an ester-containing polymer. The electrolyte comprises lithium bis(trifluoromethanesulfonyl)imide. The battery satisfies the following relationships: 0.3≤D1≤0.8, 0.1≤A≤15, 0.3≤A / D1≤48, where D1 is the average particle size of the first particles in μm, and A is the weight percentage of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte in %.

[0005] By employing the above technical solution, the present invention has at least the following advantages compared with the prior art:

[0006] In the battery of the present invention, when subjected to a heavy impact, the first polymer containing ester groups in the first particle can react with lithium bis(trifluoromethanesulfonyl)imide in the electrolyte to generate a complex with high heat resistance, thereby improving the heat resistance of the separator, delaying the thermal runaway trigger point, and increasing the battery's impact resistance. Furthermore, this complex also has compressibility and strong adhesion, which can improve or even prevent separator damage and displacement, reduce the risk of contact between the positive and negative electrodes, and further improve the battery's impact resistance. Simultaneously, by controlling the average particle size of the first particle and the weight ratio of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte, the matching degree between the first particle and lithium bis(trifluoromethanesulfonyl)imide can be improved, further enhancing the adhesion between the separator and the electrode under heavy impact conditions, forming a stable interface, preventing short circuits between the positive and negative electrodes, and improving the battery's impact resistance. Furthermore, the generated ligands can block the pores of the carrier layer, block lithium-ion transport between the positive and negative electrodes, reduce battery heat generation, delay battery thermal runaway, and further improve the impact pass rate. Moreover, it does not affect the battery's room temperature and low temperature cycling performance when no impact occurs, so that the battery has both a high impact pass rate and a high room temperature and low temperature cycling performance.

[0007] Other features and advantages of the present invention will be described in detail in the following detailed description section.

[0008] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. Attached Figure Description

[0009] Figure 1 The diagram shown is a cross-sectional schematic of the diaphragm of the present invention.

[0010] Figure 2 The diagram shown is a cross-sectional schematic of the positive electrode sheet of the present invention. Detailed Implementation

[0011] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the invention. Unless otherwise specified herein, data ranges include endpoints.

[0012] It should be noted that the numerical designations such as "first" and "second" in this invention are only used to distinguish different substances or methods of use, and do not represent a difference in order.

[0013] This invention provides a battery comprising a separator, a positive electrode, and an electrolyte. The separator includes a carrier layer and a coating on one or both surfaces of the carrier layer. The coating includes first particles, the first particles comprising a first polymer, which is an ester-containing polymer. The electrolyte comprises lithium bis(trifluoromethanesulfonyl)imide. The battery satisfies the following relationship: 0.3 ≤ D1 ≤ 0.8 (e.g., 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.6). 5, 0.7, 0.75 or 0.8), 0.1≤A≤15 (e.g. 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15), 0.3≤A / D1≤48 (e.g. 0.3, 1, 5, 10, 15, 20, 25, 30, 35, 40, 45 or 48), where D1 is the average particle size of the first particle in μm, and A is the weight percentage of the lithium bis(trifluoromethanesulfonyl)imide in the electrolyte in %.

[0014] like Figure 1 As shown, the separator may include a carrier layer 11 and a coating 12 located on one or both surfaces of the carrier layer 11. When one surface of the carrier layer has a coating, the positive electrode corresponds to the coated side of the separator. The coating 12 includes first particles 121.

[0015] The separator of the battery of the present invention includes a first particle, the composition of which includes ester groups. When the battery is subjected to a heavy impact, the first particle can absorb the heat generated by the battery. Under the action of heat, it can promote the combination of the ester groups in the first particle with lithium bis(trifluoromethanesulfonyl)imide in the electrolyte to form a high-temperature resistant complex. On the one hand, the complex can improve the heat resistance of the separator, delay the melting and local damage of the separator, prevent short circuits caused by contact between the positive and negative electrodes, postpone the thermal runaway trigger point, and improve the battery's heavy impact pass rate. On the other hand, the complex has compressibility and strong adhesion, which can improve the adhesion between the separator and the electrode (hereinafter collectively referred to as the electrode). When the battery is subjected to a heavy impact, it can prevent the separator from breaking and displacing under pressure, thus preventing the positive and negative electrodes from contacting each other and improving the battery's heavy impact pass rate.

[0016] To further improve the adhesion between the separator and the electrode under heavy impact, forming a stable interface and preventing short circuits caused by displacement between the separator and the electrode under heavy impact, and to ensure the formation of ligands that can block the pores of the carrier layer and block lithium-ion transport between the positive and negative electrodes, thereby improving the heavy impact pass rate, this invention controls the battery to satisfy the following relationships: 0.3≤D1≤0.8, 0.1≤A≤15, 0.3≤A / D1≤48. By controlling the battery to satisfy the above relationships, a better matching degree can be achieved between the first particle and lithium bis(trifluoromethanesulfonyl)imide. When a heavy impact occurs, the first particle of the above particle size generates an appropriate amount of ligands with the lithium bis(trifluoromethanesulfonyl)imide in the electrolyte. This improves the separator adhesion and the interfacial stability between the separator and the electrode, while ensuring the separator has high kinetic performance. Thus, the battery has both a high heavy impact pass rate and does not affect the battery's room temperature and low temperature cycling performance.

[0017] Understandably, without the impact of a heavy object, the first particle will not combine with the difluoromethanesulfonyl imide in the electrolyte to form a high-temperature resistant ligand, nor will it block the pores of the carrier layer and affect the transport of lithium ions between the positive and negative electrodes. Therefore, it will not have an adverse effect on the battery performance, such as room temperature cycle performance and low temperature cycle performance.

[0018] When A / D1 is higher than 48, the average particle size of the first particle is too small, resulting in an excessive weight proportion of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte. This leads to an excessively large contact area between the first particle and the electrolyte, causing it to over-swell under the solvent's influence. This results in insufficient adhesion between the separator and the electrode, high interfacial impedance, and may also lead to an excessive weight proportion of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte, which can easily corrode the positive electrode current collector, increase battery impedance, and reduce the battery's low-temperature cycle performance. When A / D1 is lower than 0.3... If the average particle size of the first particle is too large and the weight ratio of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte is too small, the contact area between the first particle and the electrolyte will be small. When subjected to heavy impact, the heat absorbed by the first particle is insufficient to generate ligands with lithium bis(trifluoromethanesulfonyl)imide, resulting in a small amount of ligands generated. Consequently, the compressibility and adhesion of the separator are insufficient during heavy impact, which is not conducive to improving the adhesion of the separator and the stability of the interface between the separator and the electrode during heavy impact, resulting in a low heavy impact pass rate of the battery.

[0019] In this invention, the average particle size of the first particle can be obtained by the following method: On a scanned image of the coating surface obtained using SEM, draw a square or rectangle with the smallest area that completely surrounds one first particle, i.e., draw a square or rectangle where the edge of the first particle is connected to the four sides of the square or rectangle. The length of one side of the square or the length of the long side of the rectangle is the particle size of the first particle. In an arbitrary 10μm*10μm area on the coating surface, measure the particle size of any 100 first particles, and average the number of measurements as the average particle size. Repeat the above operation 5 times, and take the average value as the average particle size of the first particle. It should be noted that when 100 first particles can be observed in the captured image, the average particle size of any 100 first particles in the image is taken as the average particle size of the first particle. When no 100 first particles are observed in the image, take multiple images, and average the total number of particle sizes of 100 first particles as the average particle size. The scanned images can be obtained by observing the surface of the coating using a scanning electron microscope (S-3400N manufactured by Hitachi, Ltd.).

[0020] In this invention, the weight percentage of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte can be obtained by the following method: extracting an electrolyte sample from the casing of the finished battery and performing ion chromatography on the electrolyte sample.

[0021] In this invention, by controlling the average particle size of the first particles in the separator, the weight percentage of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte, and the ratio between the two, the battery's pass rate against heavy impacts and its low-temperature cycling performance can be improved compared to existing technologies. To further enhance the effect, one or more of the technical features can be further optimized.

[0022] In one example, the battery satisfies the following relationships: 0.5≤D1≤0.75, 0.5≤A≤10, 1≤A / D1≤20.

[0023] In one example, the particle size of the first particle is 0.25 μm to 0.85 μm (e.g., 0.25 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, or 0.7 μm). It is understood that the particle size of the first particle differs from the average particle size of the first particles; the particle size of the first particle is the size of a single first particle, while the average particle size is the average size of the first particles in a system.

[0024] In one example, the first particle has a coverage of 10%-90% on the coating surface (e.g., 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, or 90%).

[0025] In one instance, the first particle has a coverage of 15%-45% on the coating surface.

[0026] In this invention, the coverage of the first particle on the coating surface can be tested by the following method, for example, by scanning electron microscopy (SEM). Specifically, a microscopic image of the coating surface is obtained using SEM, and a 10000 μm area is randomly divided in the image. 2 The area (e.g., 100μm × 100μm) is divided into uniform squares of 400*400. If the coverage area of ​​the first particle in a square exceeds half of the square area, it means that the square is occupied by the first particle; otherwise, it means that the square is not occupied by the first particle. By counting the number of squares occupied by the first particle, the total number of squares occupied by the first particle is recorded as X. Then, the coverage rate = (X / (400*400))*100%. Repeat the above operation 5 times, and take the average of the 5 times as the coverage rate of the first particle on the coating surface.

[0027] In one example, the first polymer is an ester-containing polymer and does not contain elemental fluorine.

[0028] In one example, the first polymer comprises a polymer polymerized from one or more of the following monomers: methyl methacrylate, butyl acrylate, isooctyl acrylate, octadecyl acrylate, and ethyl acrylate.

[0029] In one example, the first polymer is selected from one or more of polybutyl acrylate, polyethyl acrylate, polybutyl methacrylate, polymethyl methacrylate, methacrylate-acrylonitrile copolymer, methacrylate-ethylene copolymer, methacrylate-styrene copolymer, and butadiene-isobutyl acrylate copolymer.

[0030] In one example, the first particles are arranged in a stacked configuration within the coating. It is understood that a stacked configuration means that, in the thickness direction of the membrane, the first particles are present in only one layer or multiple layers within the coating, without the formation of large-size agglomerates.

[0031] In one example, the coating includes a second particle. For example... Figure 1 As shown, the second particle may include primary particles 1221 and / or secondary particles 1222. The secondary particles are formed by the aggregation of the first particles. In this invention, a particle formed by the aggregation of at least five primary particles is a secondary particle.

[0032] In one example, the second particle comprises a second polymer, which is a polymer formed by polymerizing one or more monomers selected from the following: vinylidene fluoride, tetrafluoroethylene, hexafluoroethylene, styrene, ethylene, propylene, acrylonitrile, methyl methacrylate, butyl acrylate, isooctyl acrylate, octadecyl acrylate, ethyl acrylate, amide, and imide. The second particle comprising the second polymer can improve the wettability of the electrolyte between the separator and the electrode, improve lithium-ion transport efficiency, and enhance the low-temperature cycle performance of the battery.

[0033] In one example, the second polymer is a fluoropolymer selected from at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl fluoride, polyhexafluoropropylene, fluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, and tetrafluoroethylene-hexafluoropropylene copolymer.

[0034] In one example, the particle size of the second particle is greater than 0.9 μm (e.g., 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm, or 20 μm). It is understood that "the particle size of the second particle is greater than 0.9 μm" means that the particle size of a single particle of the second particle is greater than 0.9 μm, or that the particle size of secondary particles of the second particle is greater than 0.9 μm, where secondary particles refer to aggregates formed by the aggregation of primary particles. When the second particle is an aggregated particle, the particle size of the primary particles of the second particle is 0.1 μm-0.2 μm (e.g., 0.1 μm, 0.13 μm, 0.15 μm, 0.18 μm, or 0.2 μm). In this invention, the particle size of the second particle can be obtained by the following method: on the scanned image of the coating surface obtained by SEM, draw the smallest square or rectangle that completely surrounds one second particle, that is, draw the square or rectangle whose edge of the second particle is connected to the four sides of the square or rectangle, and the length of one side of the square or the length of the long side of the rectangle is the particle size of the second particle.

[0035] When the coating includes both the first particle and the second particle, the first particle and the second particle can be distinguished by particle size or morphology. The first particle has a smaller particle size, while the second particle has a larger particle size or may exhibit agglomeration. Specifically, particles with a particle size > 0.9 μm are the second particles, particles with a particle size of 0.25 μm-0.85 μm are the first particles, or particles arranged in a single layer are the first particles, and particles exhibiting agglomeration are the second particles.

[0036] In one example, the number of second particles with a diameter greater than 0.9 μm in a 100 μm × 100 μm area on the separator surface is 30 to 450 (e.g., 30, 50, 100, 150, 200, 250, 300, 350, 400, or 450). The number of second particles with a diameter greater than 0.9 μm refers to the number of individual particles with a diameter greater than 0.9 μm, or the number of secondary particles with a diameter greater than 0.9 μm. Controlling the number of second particles with a diameter greater than 0.9 μm in a 100 μm × 100 μm area on the separator surface within the above range ensures the presence of larger-diameter particles in the coating, thereby reducing the risk of particles clogging the pores of the carrier layer, improving lithium-ion transport performance, and further enhancing the low-temperature cycling performance of the battery.

[0037] In this invention, the measurement of the number of secondary particles of the second particle in a 100μm×100μm area on the surface of the diaphragm can be performed by arbitrarily selecting a 100μm×100μm area on the surface of the diaphragm, counting the number of secondary particles of the second particle, repeating the operation 5 times, and taking the average value as the final measurement result.

[0038] In one example, the average particle size of the second particle is 3μm-15μm (e.g., 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm or 13μm).

[0039] In one instance, the coating includes a second adhesive.

[0040] In one example, the second adhesive comprises one or more of polyvinyl alcohol, styrene-butadiene rubber, ethylene-vinyl acetate copolymer, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polymethyl methacrylate, polybutyl methacrylate, styrene-acrylic latex, polyacrylonitrile, ethyl polyacrylate, polyvinyl acetate, polyacrylate, polyvinylidene fluoride polyurethane, polyvinylidene fluoride-hexafluoropropylene, or copolymer systems derived from the above polymers.

[0041] In one instance, such as Figure 1 As shown, the carrier layer 11 includes a substrate layer 111 and a heat-resistant layer 112 located on one or both sides of the substrate layer 111.

[0042] In one example, the diaphragm includes a substrate layer, a heat-resistant layer, and a coating, the heat-resistant layer being located on one side surface of the substrate layer, and the coating being located on the surface of the heat-resistant layer and the other side surface of the substrate layer.

[0043] In one example, the diaphragm includes a substrate layer, a heat-resistant layer, and a coating, the heat-resistant layer being located on one side surface of the substrate layer and the coating being located on the other side surface of the substrate layer.

[0044] In one example, the diaphragm includes a substrate layer, a heat-resistant layer, and a coating layer, the heat-resistant layer being located on both sides of the substrate layer, and the coating layer being located on the surface of the heat-resistant layer.

[0045] In one example, the heat-resistant layer comprises a third particle and a first binder, wherein the third particle comprises one or more of boehmite (γ-AlOOH), alumina (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), silicon dioxide (SiO2), tin dioxide (SnO2), titanium dioxide (TiO2), calcium oxide (CaO), zinc oxide (ZnO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), nickel oxide (NiO), cerium oxide (CeO2), zirconium titanate (SrTiO3), barium titanate (BaTiO3), magnesium fluoride (MgF2), melamine cyanurate, and lithium aluminum titanium phosphate.

[0046] In one example, the first adhesive comprises one or more of polyvinyl alcohol, styrene-butadiene rubber, ethylene-vinyl acetate copolymer, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polymethyl methacrylate, polybutyl methacrylate, styrene-acrylic latex, polyacrylonitrile, ethyl polyacrylate, polyvinyl acetate, polyacrylate, polyvinylidene fluoride polyurethane, polyvinylidene fluoride-hexafluoropropylene, or copolymer systems derived from the above polymers.

[0047] In one example, based on the total weight of the heat-resistant layer, the third particle accounts for 50%-99% by weight (e.g., 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or 99%), and the first adhesive accounts for 1%-50% by weight (e.g., 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or 50%).

[0048] In one example, the thickness of the heat-resistant layer is 0.2 μm to 5 μm (e.g., 0.2 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm).

[0049] In one example, the porosity of the substrate layer is 30%-45% (e.g., 30%, 33%, 35%, 38%, 40%, 43%, or 45%). Controlling the porosity of the substrate layer within this range enables the membrane to maintain high strength and reduces the risk of short circuits between the positive and negative electrodes.

[0050] In this invention, the porosity of the substrate layer can be tested using the following method: The separator is removed from the battery cell, and the separator is selected from the head, tail, or superanode region of the cell, where it is not bonded to the electrode and the coating has not transferred to the electrode surface. The separator is cleaned with NMP to remove electrolyte and residual lithium salt, and then placed in a 40°C vacuum oven to dry and remove solvent, obtaining a separator test sample. The coating is then peeled off from the separator test sample using 3M tape, leaving the substrate layer. The porosity of the substrate layer is measured using a true density meter.

[0051] In one example, the substrate layer comprises one or more of the following: polyolefin, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinyl chloride, polytetrafluoroethylene, polyacrylonitrile, polymethyl methacrylate, polyimide, polyetheretherketone, polyethylene terephthalate, polybutylene terephthalate, poly(p-phenylene terephthalamide), poly(m-phenylene isophthalamide), cellulose, polyurethane, poly(p-phenylenebenzodiazole), polyetherimide, polyphenylene sulfide, or copolymer systems derived from the above polymers.

[0052] In one example, the thickness of the substrate layer is 3μm-12μm (e.g., 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm or 12μm).

[0053] In one example, the puncture strength of the diaphragm is 250gf-600gf (e.g., 250gf, 300gf, 350gf, 400gf, 450gf, 500gf, 550gf or 600gf).

[0054] In this invention, the puncture strength of the separator can be tested by the following method: The separator is removed from the battery cell, and the separator is selected from the head, tail, or superanode region of the cell, where it is not bonded to the electrode and the coating has not transferred to the electrode surface. The separator is cleaned with NMP to remove electrolyte and residual lithium salt, and then placed in a 40°C vacuum oven to dry and remove solvent, obtaining a separator test sample. The sample is measured using a universal tensile testing machine with a fixture aperture of Φ10mm±0.5mm. A round-tipped probe with a radius of 0.5mm is used, advancing towards the plane of the separator test sample at a speed of 100mm / min. The maximum force with which the probe punctures the membrane is the puncture strength.

[0055] In one example, the electrolyte comprises propylene carbonate and fluoroethylene carbonate, and the battery satisfies the following relationship: 0.1 ≤ B / C ≤ 0.8 (e.g., 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, or 0.8), where B is the weight percentage of propylene carbonate in the electrolyte, and C is the weight percentage of fluoroethylene carbonate in the electrolyte. Controlling the battery to satisfy the above relationship can further promote the bonding between the first polymer and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) without affecting the battery's room temperature performance, thereby improving the stability of the interface between the separator and the electrode, and enhancing the battery's impact resistance.

[0056] In one example, the weight percentage B of the propylene carbonate in the electrolyte is 2%-20% (e.g., 2%, 5%, 7%, 10%, 12%, 15%, 17% or 20%).

[0057] In one example, the weight percentage C of the fluoroethylene carbonate in the electrolyte is 2%-30% (e.g., 2%, 5%, 7%, 10%, 12%, 15%, 17%, 20%, 22%, 25%, 27% or 30%).

[0058] According to one specific implementation, B is 2%-20%, C is 2%-30%, and the battery satisfies the following relationship: 0.1≤B / C≤0.8.

[0059] In one example, the electrolyte comprises lithium hexafluorophosphate, wherein the weight percentage of the lithium hexafluorophosphate in the electrolyte is 12%-23% (e.g., 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22% or 23%).

[0060] According to one specific embodiment, the porosity of the substrate layer is 30%-45%, and the weight percentage of lithium hexafluorophosphate in the electrolyte is 12%-23%. Simultaneously controlling the porosity of the substrate layer and the weight percentage of lithium hexafluorophosphate in the electrolyte can increase the lithium-ion concentration, reduce the negative impact of lower porosity on the lithium-ion transport rate, improve lithium-ion transport efficiency, and also maintain high membrane strength, reducing the risk of short circuits between the positive and negative electrodes.

[0061] In one example, the electrolyte also includes organic solvents and additives.

[0062] In one example, the lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, lithium tetrafluoroborate, lithium di(oxalate)borate, lithium di(fluorooxalate)borate, and lithium di(fluorobis(oxalate))phosphate.

[0063] In one example, the organic solvent refers to a solvent other than propylene carbonate, including one or more of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl formate (MF), methyl acetate (MA), methyl butyrate (MB), ethyl propionate (EP), propyl propionate (PP), ethyl butyrate, propyl acetate, and ethyl difluoroacetate.

[0064] In one example, the additive refers to an additive other than fluoroethylene carbonate, including film-forming additives for the negative electrode surface, film-forming additives for the positive electrode surface, and film-forming additives for the positive and negative electrode current collector surfaces; it may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc. The additive can be one or more of the following: dinitrile compounds, trinitrile compounds, fluorinated chain carbonates, and sulfur-containing compounds.

[0065] Dinitrile compounds include, but are not limited to: succinic anion, glutaronitrile, adiponitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, 1,7-dicyanoheptane, 1,8-dicyanoctane, 1,9-dicyanonane, 1,10-dicyanodecane, 1,12-dicyanododecane, tetramethylsuccinic anion, 2-methylglutaronitrile, 2,4-dimethylpentane, 2,2,4,4-tetramethylglutaronitrile, 1,5-dicyanopentane, 2,6-dicyanoheptane, 2,7-dicyanoctane, 2,8-dicyanonane, 1,6-dicyanodecane, 1,2-dicyanobenzene, 1,3-dicyanobenzene, 1,4-dicyanobenzene, triethylene glycol di(2-cyano) The following are some of the following: di(2-cyanoethyl) ether, tetraethylene glycol di(2-cyanoethyl) ether, 3,6,9,12,15,18-hexaoxaneicosanoic acid dionitrile, 1,3-di(2-cyanoethoxy)propane, 1,4-di(2-cyanoethoxy)butane, 1,5-di(2-cyanoethoxy)pentane, ethylene glycol di(4-cyanobutyl) ether, 1,4-dicyano-2-butene, 1,4-dicyano-2-methyl-2-butene, 1,4-dicyano-2,3-diethyl-2-butene, 1,6-dicyano-3-hexene, 1,6-dicyano-2-methyl-3-hexene, or 1,6-dicyano-2-methyl-5-methyl-3-hexene.

[0066] Trinitrile compounds include, but are not limited to, one or more of the following: 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,3,6-hexanetricarbonitrile, 1,2,6-hexanetricarbonitrile, 1,2,3-tris(2-cyanoethoxy)propane, 1,2,4-tris(2-cyanoethoxy)butane, 1,1,1-tris(cyanoethoxymethylene)ethane, 1,2,7-tris(cyanoethoxy)heptane, 1,2,6-tris(cyanoethoxy)hexane, or 1,2,5-tris(cyanoethoxy)pentane.

[0067] Sulfur-containing compounds include, but are not limited to, one or more of the following: 1,3-propanesulfonate lactone, vinyl sulfate, cyclic sulfate, chain sulfonate, cyclic sulfonate, chain sulfite, cyclic sulfite, and cyclic sulfone.

[0068] Fluorinated chain carbonates include, but are not limited to, one or more of the following: fluoromethyl methyl carbonate, difluoromethyl methyl carbonate, trifluoromethyl methyl carbonate, trifluoroethyl methyl carbonate, or bis(trifluoroethyl) carbonate.

[0069] In one example, based on the total weight of the electrolyte, the lithium salt comprises 12%-30% by weight (e.g., 12%, 15%, 20%, 25%, or 30%), the organic solvent comprises 0%-60% by weight (e.g., 0, 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, or 60%), and the additive comprises 0%-30% by weight (e.g., 0, 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, or 30%). When the weight percentage of the organic solvent in the electrolyte is 0, it indicates that there is no organic solvent other than propylene carbonate in the electrolyte. When the weight percentage of the additive in the electrolyte is 0, it indicates that there are no additives other than fluoroethylene carbonate in the electrolyte.

[0070] In one instance, such as Figure 2 As shown, the positive electrode sheet includes a positive current collector 1 and a positive active layer 2. The positive active layer 2 is located on both sides of the positive current collector 1. In the thickness direction of the positive electrode sheet, the positive electrode sheet includes a first surface 3 and a second surface 4 that are opposite to the positive current collector. The first surface 3 includes a plurality of recesses 5. The first surface 3 corresponds to the coating 12.

[0071] It is understood that when the coating is located on one side of the carrier layer, the first surface corresponds to the coating. When the coating is located on both sides of the carrier layer, both the first surface and the second surface correspond to the coating.

[0072] In one example, the battery satisfies the following relationship: 1 ≤ H / R ≤ 40 (e.g., 1, 3, 5, 8, 10, 13, 15, 18, 20, 23, 25, 28, 30, 33, 35, 38, or 40). Wherein, H is the depth of the recessed portion in μm, and R is the diameter of the recessed portion in mm. A certain amount of electrolyte can be stored in the recessed portion. Lithium bis(trifluoromethanesulfonyl)imide in the electrolyte corrodes the positive electrode current collector. Therefore, controlling the battery to satisfy the above relationship enables directional fracture of the positive electrode recess when the battery is subjected to a heavy impact, i.e., fracture preferentially occurs in the recessed portion. This reduces burrs at the fracture site, improves or even avoids the risk of battery fire and / or explosion, and improves battery safety performance. When the H / R ratio is below 1, the electrolyte stored in the recess is less, resulting in poor corrosion of the positive electrode current collector. Under heavy impact, it cannot form a directional fracture in the recess, thus offering little protection against impact damage. When the H / R ratio is above 40, the positive electrode current collector experiences greater tensile stress, making it more prone to fracture during battery cycling, thus reducing battery safety. It is understandable that while lithium bis(trifluoromethanesulfonyl)imide in the electrolyte does have some corrosive effect on the positive electrode current collector, this effect is weak. Furthermore, due to the thinness of the positive electrode active layer in the recess, lithium bis(trifluoromethanesulfonyl)imide only exerts a certain degree of corrosion on the current collector. In areas with a thicker positive electrode active layer, lithium bis(trifluoromethanesulfonyl)imide essentially does not corrode the current collector. Therefore, the corrosive effect of lithium bis(trifluoromethanesulfonyl)imide on the positive electrode current collector does not affect normal battery use. Only under heavy impact can it assist in directional fracture of the positive electrode current collector, improving battery safety.

[0073] In one instance, the battery satisfies the following relationship: 2 ≤ H / R ≤ 15.

[0074] In one example, the depth H of the recess is 3μm-45μm (e.g., 3μm, 5μm, 8μm, 10μm, 13μm, 15μm, 18μm, 20μm, 23μm, 25μm, 28μm, 30μm, 33μm, 35μm, 38μm, 40μm, 43μm or 45μm).

[0075] In one example, the depth H of the recess is 4μm-25μm.

[0076] In this invention, the depth of the recess is the vertical distance from the lowest point of the recess to the first surface in the thickness direction of the positive electrode sheet.

[0077] In one example, the diameter R of the recess is 1mm-5mm (e.g., 1mm, 1.5mm, 2mm, 2.5mm, 3mm, 3.5mm, 4mm, 4.5mm or 5mm).

[0078] In one example, the diameter R of the recess is 1.5mm-3mm.

[0079] In this invention, the diameter of the recess is the maximum distance between any two points on the orthographic projection of the recess onto the first surface.

[0080] In one example, the spacing D between adjacent recesses is 0.5mm-8mm (e.g., 0.5mm, 1mm, 2mm, 3mm, 4mm, 5mm, 6mm, 7mm, or 8mm). In this invention, the spacing between adjacent recesses refers to the shortest distance between the two adjacent edge lines of two adjacent recesses.

[0081] In one example, the second surface 4 is provided with a plurality of protrusions 6.

[0082] In this invention, the recessed portion of the first surface and the protruding portion of the second surface can be obtained through an embossing process.

[0083] In one example, the positive electrode active layer includes a positive electrode active material, a positive electrode conductive agent, and a positive electrode binder.

[0084] In one example, the positive electrode active material includes one or more of lithium nickel oxide, lithium titanate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium manganese oxide.

[0085] In one example, the positive electrode conductive agent includes one or more of conductive carbon black (Super P), carbon nanotubes, conductive graphite, and graphene.

[0086] In one example, the positive electrode binder includes one or more of polyvinylidene fluoride (PVDF), acrylic-modified PVDF, polyacrylate polymers, polyimide, styrene-butadiene rubber, and styrene-acrylic rubber.

[0087] In one example, based on the total weight of the positive electrode active layer, the weight percentage of the positive electrode active material is 80%-99.8% (e.g., 80%, 83%, 85%, 88%, 90%, 93%, 95%, 98%, or 99.8%), the weight percentage of the positive electrode conductive agent is 0.1%-10% (e.g., 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%), and the weight percentage of the positive electrode binder is 0.1%-10% (e.g., 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%).

[0088] In one example, the battery also includes a negative electrode.

[0089] The negative electrode sheet can be a conventional negative electrode sheet in the art. For example, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer located on one or both sides of the surface of the negative electrode current collector.

[0090] In one example, the battery is a lithium-ion rechargeable battery.

[0091] The present invention will be described in detail below through embodiments. The embodiments described herein are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0092] The following examples illustrate the battery of the present invention.

[0093] Example I illustrates that the surface of the positive electrode sheet of the present invention does not have recesses or protrusions.

[0094] Example I-1

[0095] (1) Diaphragm

[0096] The third particle (alumina) and the first binder (polymethyl methacrylate) were mixed and stirred thoroughly to obtain a mixed slurry with a solid content of 25%. The slurry was coated on one side of the substrate layer (PE, 5.1 μm thick, 37.1% porosity) using a gravure roller with a 100% solid mass ratio of alumina:polymethyl methacrylate = 95:5. After drying in a multi-section oven at 60°C, a heat-resistant layer with a thickness of 2.5 μm was formed. The first particle (PMMA), the second particle (polyvinylidene fluoride), and the second binder (polyacrylate) (the weight ratio of the first particle:the second particle:the second binder was 35:60:5) were dispersed in deionized water and stirred thoroughly to obtain a slurry with a solid content of 10%. The slurry was coated on the surface of the heat-resistant layer and the other side of the substrate layer using a gravure roller.

[0097] The average particle size D1 of the first particle is 0.6 μm, the coverage of the first particle on the coating surface is 27.4%, the number of the second particles with a particle size greater than 0.9 μm in the 100 μm × 100 μm area of ​​the diaphragm surface is 263, and the puncture strength of the diaphragm is 300 gf.

[0098] (2) Positive electrode plate

[0099] Lithium cobalt oxide, polyvinylidene fluoride (PVDF 500) as the positive electrode binder, and a positive electrode conductive agent (Super P: carbon nanotubes (weight ratio) = 2:1) were mixed in N-methylpyrrolidone (NMP) solvent at a weight ratio of 97.5:1:1.5 and continuously stirred under the action of a stirrer to form a homogeneous and fluid positive electrode slurry. Subsequently, the positive electrode slurry was coated on both sides of an aluminum foil with a thickness of 10 μm and an elongation of 2%, and dried in a vacuum oven at 120°C for 6 hours. After that, it was rolled and slit to obtain the positive electrode sheet.

[0100] (3) Negative electrode sheet

[0101] Graphite, silicon carbide (Dv50 = 3 μm), conductive carbon black (Super P), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber were mixed in an aqueous solvent at a weight ratio of 91:7:1:0.5:0.5 and continuously stirred under the action of a stirrer to form a homogeneous and fluid negative electrode slurry. Subsequently, the slurry was coated on both sides of a 10 μm thick current collector copper foil and dried in a vacuum oven at 120°C for 6 hours. After that, it was rolled and slit to obtain the negative electrode sheet.

[0102] (4) Electrolyte

[0103] In an argon-filled glove box (moisture <1 ppm, oxygen <1 ppm), ethylene carbonate, propylene carbonate, propyl propionate, and ethyl propionate solvents were mixed to form a homogeneous solvent. LiPF6, lithium bis(trifluoromethanesulfonyl)imide, 1,3-propanesulfonyl lactone, 1,3,6-hexanetrionitrile, and fluoroethylene carbonate were slowly added and stirred until homogeneous to obtain the electrolyte. In the electrolyte, LiPF6 accounted for 18% by weight, lithium bis(trifluoromethanesulfonyl)imide (A) accounted for 4.8% by weight, propylene carbonate (B) accounted for 10% by weight, fluoroethylene carbonate (C) accounted for 20% by weight, 1,3-propanesulfonyl lactone accounted for 2% by weight, 1,3,6-hexanetrionitrile accounted for 3% by weight, and the weight ratio of ethylene carbonate:propyl propionate:ethyl propionate was 15:50:20, and B / C = 10 / 20 = 0.5.

[0104] (5) Lithium-ion batteries

[0105] The positive electrode sheet obtained in step (2), the separator obtained in step (1), and the negative electrode sheet obtained in step (3) are wound together to form a bare battery cell. Then, the bare battery cell is placed in an aluminum-plastic film, and the electrolyte obtained in step (4) is injected into the dried bare battery cell. After vacuum sealing, room temperature standing, and high temperature formation, a lithium-ion battery is obtained. Among them, A / D1 = 4.8 / 0.6 = 8.

[0106] Example 1-2 group

[0107] This set of examples illustrates the effects of a change in the average particle size D1 of the first particle.

[0108] Example I-2a

[0109] The experiment was carried out in accordance with Example I-1, except that D1 was 0.3 μm and A / D1 = 4.8 / 0.3 = 16.

[0110] Example I-2b

[0111] The experiment was carried out in accordance with Example I-1, except that D1 was 0.74 μm and A / D1 = 4.8 / 0.74 = 6.49.

[0112] Example I-2c

[0113] The experiment was carried out in accordance with Example I-1, except that D1 was 0.52 μm and A / D1 = 4.8 / 0.52 = 9.23.

[0114] Example I-2d

[0115] The experiment was carried out in accordance with Example I-1, except that D1 was 0.79 μm and A / D1 = 4.8 / 0.79 = 6.08.

[0116] Example 1-3 group

[0117] This set of examples illustrates the effects of changing the weight percentage A of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte.

[0118] Example I-3a

[0119] The same procedure was performed as in Example I-1, except that A was 0.2% and A / D1 = 0.2 / 0.6 = 0.33.

[0120] Example I-3b

[0121] The same procedure was performed as in Example I-1, except that A was 0.64% and A / D1 = 0.64 / 0.6 = 1.07.

[0122] Example I-3c

[0123] The same procedure was performed as in Example I-1, except that A was 15% and A / D1 = 15 / 0.6 = 25.

[0124] Example 1-4 group

[0125] This set of examples illustrates the effects of changes in A / D1.

[0126] Example I-4a

[0127] The experiment was carried out in accordance with Example I-1, except that A was 10%, D1 was 0.52 μm, and A / D1 = 10 / 0.52 = 19.23.

[0128] Example I-4b

[0129] The experiment was conducted in accordance with Example I-1, except that A was 14.3%, D1 was 0.3 μm, and A / D1 = 14.3 / 0.3 = 47.67.

[0130] Example 1-5 group

[0131] This set of examples illustrates the effects of changes in the coverage of the first particle on the coating surface.

[0132] Example I-5a

[0133] The same procedure was followed as in Example I-1, except that the first particle had a coverage of 10.4% on the coating surface.

[0134] Example I-5b

[0135] The same procedure was followed as in Example I-1, except that the first particle had a coverage rate of 15.1% on the coating surface.

[0136] Example I-5c

[0137] The same procedure was performed as in Example I-1, except that the first particle had a coverage rate of 44.8% on the coating surface.

[0138] Example I-5d

[0139] The same procedure was performed as in Example I-1, except that the first particle had a coverage rate of 89.5% on the coating surface.

[0140] Example 1-6 group

[0141] This set of examples illustrates the effect of changing the number of second particles with a diameter greater than 0.9 μm in a 100 μm × 100 μm area on the surface of the diaphragm.

[0142] Example I-6a

[0143] The procedure was carried out in accordance with Example I-1, except that the number of second particles with a diameter greater than 0.9 μm in a 100 μm × 100 μm area on the surface of the diaphragm was 34.

[0144] Example I-6b

[0145] The procedure was carried out in accordance with Example I-1, except that the number of second particles with a diameter greater than 0.9 μm in a 100 μm × 100 μm area on the surface of the diaphragm was 448.

[0146] Example 1-7 group

[0147] This set of examples illustrates the effects that occur when the composition of the first particle changes.

[0148] Example I-7a

[0149] The procedure was carried out in accordance with Example I-1, except that the first particle was composed of polybutyl polyacrylate.

[0150] Example I-7b

[0151] The procedure was carried out in accordance with Example I-1, except that the first particle was composed of isooctyl polyacrylate.

[0152] Example 1-8 group

[0153] This set of examples illustrates the effects that occur when the composition of the second particle changes.

[0154] Example I-8a

[0155] The procedure was carried out in accordance with Example I-1, except that the second particle was composed of polyethylene.

[0156] Example I-8b

[0157] The procedure was carried out in accordance with Example I-1, except that the second particle was composed of polyhexafluoroethylene.

[0158] Example 1-9

[0159] This set of examples illustrates the effects that occur when the composition of the third particle changes.

[0160] Example I-9a

[0161] The procedure was carried out in accordance with Example I-1, except that the third particle was composed of melamine cyanuric acid.

[0162] Example I-9b

[0163] The procedure was carried out in accordance with Example I-1, except that the third particle was composed of lithium aluminum titanium phosphate.

[0164] Example I-10 group

[0165] This set of examples illustrates the effects of changes in the thickness of the heat-resistant layer and / or the substrate layer.

[0166] Example I-10a

[0167] The same procedure was followed as in Example I-1, except that the thickness of the heat-resistant layer was 5 μm and the thickness of the substrate layer was 12 μm.

[0168] Example I-10b

[0169] The same procedure was followed as in Example I-1, except that the thickness of the heat-resistant layer was 0.2 μm and the thickness of the substrate layer was 3 μm.

[0170] Example I-11 group

[0171] This set of examples illustrates the effects of changes in the porosity of the substrate layer and / or the weight percentage of lithium hexafluorophosphate in the electrolyte.

[0172] Example I-11a

[0173] The experiment was conducted in accordance with Example I-1, except that the porosity of the substrate layer was 30.4% and the weight percentage of lithium hexafluorophosphate in the electrolyte was 12%.

[0174] Example I-11b

[0175] The experiment was conducted in accordance with Example I-1, except that the porosity of the substrate layer was 44.7% and the weight percentage of lithium hexafluorophosphate in the electrolyte was 23%.

[0176] Example I-11c

[0177] The experiment was conducted in accordance with Example I-1, except that the porosity of the substrate layer was 28.1% and the weight percentage of lithium hexafluorophosphate in the electrolyte was 11.8%.

[0178] Example I-11d

[0179] The experiment was conducted in accordance with Example I-1, except that the porosity of the substrate layer was 45.8% and the weight percentage of lithium hexafluorophosphate in the electrolyte was 23.5%.

[0180] Example I-12 group

[0181] This set of examples illustrates the effects of changes in B / C.

[0182] Example I-12a

[0183] The process was carried out in accordance with Example I-1, except that the weight percentage B of propylene carbonate in the electrolyte was 2%, and the weight percentage C of fluoroethylene carbonate in the electrolyte was 20%, with B / C = 2% / 20% = 0.1.

[0184] Example I-12b

[0185] The experiment was conducted in accordance with Example I-1, except that the weight percentage B of the propylene carbonate in the electrolyte was 20%, and the weight percentage C of the fluoroethylene carbonate in the electrolyte was 20%, with B / C = 20% / 20% = 1.

[0186] Example I-12c

[0187] The process was carried out in accordance with Example I-1, except that the weight percentage B of the propylene carbonate in the electrolyte was 10%, and the weight percentage C of the fluoroethylene carbonate in the electrolyte was 2%, with B / C = 10% / 2% = 5.

[0188] Example I-12d

[0189] The experiment was conducted in accordance with Example I-1, except that the weight percentage B of the propylene carbonate in the electrolyte was 10%, and the weight percentage C of the fluoroethylene carbonate in the electrolyte was 30%, with B / C = 10% / 30% = 0.33.

[0190] Example I-12e

[0191] The experiment was conducted in accordance with Example I-1, except that the weight percentage B of propylene carbonate in the electrolyte was 8%, and the weight percentage C of fluoroethylene carbonate in the electrolyte was 10%, with B / C = 8% / 10% = 0.8.

[0192] Example I-12f

[0193] The experiment was conducted in accordance with Example I-1, except that the weight percentage B of propylene carbonate in the electrolyte was 1.3%, and the weight percentage C of fluoroethylene carbonate in the electrolyte was 1.8%, with B / C = 1.3% / 1.8% = 0.72.

[0194] Comparative Example I-1

[0195] The procedure was carried out in accordance with Example I-1, except that the weight percentage A of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte was 0.

[0196] Comparative Example I-2

[0197] The experiment was conducted in accordance with Example I-1, except that the weight percentage A of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte was 16%, and A / D1 = 16 / 0.6 = 26.67.

[0198] Comparative Example I-3

[0199] The procedure was carried out in accordance with Example I-1, except that the average particle size D1 of the first particle was 0.23 μm and A / D1 = 4.8 / 0.23 = 20.87.

[0200] Comparative Example I-4

[0201] The procedure was carried out in accordance with Example I-1, except that the average particle size D1 of the first particle was 0.85 μm and A / D1 = 4.8 / 0.85 = 5.65.

[0202] Comparative Example I-5

[0203] The experiment was conducted in accordance with Example I-1, except that the weight percentage A of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte was 0.1%, the average particle size D1 of the first particle was 0.69 μm, and A / D1 = 0.1 / 0.69 = 0.14.

[0204] Comparative Example I-6

[0205] The experiment was conducted in accordance with Example I-1, except that the weight percentage A of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte was 15%, the average particle size D1 of the first particle was 0.3 μm, and A / D1 = 15 / 0.3 = 50.

[0206] Test Case I

[0207] 1. Low-temperature cycling test

[0208] At 0°C, the lithium-ion battery was left to stand for 30 minutes; it was then charged at a constant current rate of 0.5C to 4.5V, and then charged at a constant voltage rate of 4.5V to 0.05C; the battery was left to stand in a 0°C environment for 24 hours; the battery was then discharged at a constant current rate of 0.5C to 3.0V, and the battery discharge capacity was recorded; this constitutes one complete intermittent charge-discharge cycle, and the battery was charged and discharged in the same manner 300 times.

[0209] Capacity retention rate (%) of a lithium-ion battery after 300 cycles = (Discharge capacity after 300 cycles / Initial discharge capacity) × 100%

[0210] 2. Impact test

[0211] In an environment of 25℃±5℃, the battery was discharged at 0.5C to the lower limit voltage (3V); after standing for 10 minutes, it was charged at a constant current of 0.7C to the upper limit voltage (4.5V), and then charged at a constant current until the cutoff current was 0.02C. This is a fully charged battery (100% SOC). After the battery is fully charged, it is discharged at 0.5C for 24 minutes (at which point the battery is 80% SOC). A metal rod with a diameter of 15.8mm±0.2mm is placed horizontally on the upper surface of the battery's geometric center. A 9.1kg weight is dropped from a height of 610mm to strike the surface of the battery with the metal rod. If the battery does not catch fire or explode, it is considered to have passed the test. If the battery catches fire and / or explodes, it is considered to have failed the test. A total of 20 sample batteries were tested for each example and comparative example. The test results are expressed as "number of passes / 20", where "20 / 20" means that all 20 batteries passed the test, and "10 / 20" means that 10 out of 20 batteries passed the test.

[0212] The results are recorded in Table 1.

[0213] Table 1

[0214]

[0215]

[0216] As can be seen from Table 1, by comparing the comparative example and the embodiment, the low-temperature cycling performance of the battery in the embodiment is improved and the pass rate of the heavy object impact test is significantly improved. This indicates that by controlling the average particle size of the first particle in the separator, the weight ratio of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte, and the ratio between the two, the low-temperature cycling performance of the battery can be maintained while improving the pass rate of the battery in the heavy object impact test.

[0217] Example II illustrates that the surface of the positive electrode sheet of the present invention has recessed portions and raised portions.

[0218] Example II-1

[0219] The process is carried out in accordance with Example I-1, except that a number of recesses are formed on the first surface of the positive electrode sheet by embossing, and a number of protrusions are formed on the second surface. The depth H of the recesses is 15 μm, the diameter R of the recesses is 2.3 mm, and H / R = 15 / 2.3 = 6.5.

[0220] Example II-2 group

[0221] This set of examples illustrates the effects that occur when H changes.

[0222] Example II-2a

[0223] The experiment was carried out in accordance with Example II-1, except that H was 3.1 μm and H / R = 3.1 / 2.3 = 1.3.

[0224] Example II-2b

[0225] The experiment was carried out in accordance with Example II-1, except that H was 4.2 μm and H / R = 4.2 / 2.3 = 1.8.

[0226] Example II-2c

[0227] The procedure was carried out in accordance with Example II-1, except that H was 25 μm and H / R = 25 / 2.3 = 10.9.

[0228] Example II-2d

[0229] The procedure was carried out in accordance with Example II-1, except that H was 45 μm and H / R = 45 / 2.3 = 19.6.

[0230] Example II-2e

[0231] The procedure was carried out in accordance with Example II-1, except that H was 5 μm and H / R = 5 / 2.3 = 2.2.

[0232] Example II-3 group

[0233] This set of examples illustrates the effects that occur when R changes.

[0234] Example II-3a

[0235] The procedure was carried out in accordance with Example II-1, except that R was 1 mm and H / R = 15 / 1 = 15.

[0236] Example II-3b

[0237] The procedure was carried out in accordance with Example II-1, except that R was 1.5 mm and H / R = 15 / 1.5 = 10.

[0238] Example II-3c

[0239] The procedure was carried out in accordance with Example II-1, except that R was 3 mm and H / R = 15 / 3 = 5.

[0240] Example II-3d

[0241] The procedure was carried out in accordance with Example II-1, except that R was 5 mm and H / R = 15 / 5 = 3.

[0242] Example II-4 group

[0243] This set of examples illustrates the effects of changes in the H / R ratio.

[0244] Example II-4a

[0245] The procedure was carried out in accordance with Example II-1, except that H was 40 μm, R was 1 mm, and H / R = 40 / 1 = 40.

[0246] Example II-4b

[0247] The same procedure was performed as in Example II-1, except that H was 41 μm, R was 1 mm, and H / R = 41 / 1 = 41.

[0248] Example II-4c

[0249] The procedure was carried out in accordance with Example II-1, except that H was 3.1 μm, R was 4 mm, and H / R = 3.1 / 4 = 0.8.

[0250] Example II-4d

[0251] The procedure was carried out in accordance with Example II-1, except that H was 2.5 μm, R was 0.8 mm, and H / R = 2.5 / 0.8 = 3.1.

[0252] Example II-4a

[0253] The experiment was carried out in accordance with Example II-1, except that H was 45.5 μm, R was 5.6 mm, and H / R = 45.5 / 5.6 = 8.1.

[0254] Test Case II

[0255] 1. Impact test

[0256] At 25℃±5℃, the battery was discharged at 0.5C to the lower limit voltage (3V); after standing for 10 minutes, it was charged at a constant current of 0.7C to the upper limit voltage (4.5V), and then charged at a constant current until the cutoff current was 0.02C. This indicates that the battery is fully charged (100% SOC). After the battery is fully charged, a metal rod with a diameter of 15.8mm±0.2mm was placed horizontally on the upper surface of the battery's geometric center. A 9.1kg weight was dropped from a height of 610mm to strike the surface of the battery with the metal rod. If the battery does not catch fire or explode, it is considered to have passed. If the battery catches fire and / or explodes, it is considered to have failed. A total of 20 batteries were tested. The test results are expressed as "number of passes / 20", where "20 / 20" means that all 20 batteries passed the test, and "10 / 20" means that 10 out of 20 batteries passed the test.

[0257] The results are recorded in Table 2.

[0258] Table 2

[0259]

[0260]

[0261] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A battery, characterized in that, The battery includes a separator, a positive electrode, and an electrolyte. The separator includes a carrier layer and a coating on one or both sides of the carrier layer. The coating includes first particles, the first particles being composed of a first polymer, which is an ester-containing polymer. The electrolyte includes lithium bis(trifluoromethanesulfonyl)imide. The battery satisfies the following relationships: 0.3≤D1≤0.8, 0.1≤A≤15, 0.3≤A / D1≤48, where D1 is the average particle size of the first particles in μm, and A is the weight percentage of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte in %.

2. The battery according to claim 1, wherein, The electrolyte comprises propylene carbonate and fluoroethylene carbonate, and the battery satisfies the following relationship: 0.1≤B / C≤0.8, where B is the weight percentage of propylene carbonate in the electrolyte and C is the weight percentage of fluoroethylene carbonate in the electrolyte. Preferably, the weight percentage B of propylene carbonate in the electrolyte is 2%-20%; Preferably, the weight percentage (C) of the fluoroethylene carbonate in the electrolyte is 2%-30%.

3. The battery according to claim 1, wherein, The positive electrode sheet includes a positive current collector and a positive active layer. In the thickness direction of the positive electrode sheet, the positive electrode sheet includes a first surface and a second surface that are opposite to the positive current collector. The first surface includes a plurality of recesses. The first surface corresponds to the coating. The battery satisfies the following relationship: 1≤H / R≤40, preferably 2≤H / R≤15, where H is the depth of the recess in μm and R is the diameter of the recess in mm.

4. The battery according to claim 3, wherein, The depth H of the recess is 3μm-45μm, preferably 4μm-25μm; And / or, the diameter R of the recess is 1mm-5mm, preferably 1.5mm-3mm; And / or, the second surface is provided with a plurality of protrusions.

5. The battery according to claim 1, wherein, The particle size of the first particle is 0.25μm-0.85μm; And / or, the first polymer comprises a polymer polymerized from one or more of the following monomers: methyl methacrylate, butyl acrylate, isooctyl acrylate, octadecyl acrylate, and ethyl acrylate. And / or, the first particle has a coverage of 10%-90% on the coating surface.

6. The battery according to any one of claims 1-5, wherein, The coating includes second particles with a particle size greater than 0.9 μm. In a 100 μm × 100 μm area on the surface of the diaphragm, the number of second particles with a particle size greater than 0.9 μm is 30 to 450. And / or, the carrier layer includes a substrate layer and a heat-resistant layer located on one or both surfaces of the substrate layer, wherein the porosity of the substrate layer is 30%-45%.

7. The battery according to claim 6, wherein, The second particle comprises a second polymer, which is a polymer formed by polymerization of one or more of the following monomers: vinylidene fluoride, tetrafluoroethylene, hexafluoroethylene, styrene, ethylene, propylene, acrylonitrile, methyl methacrylate, butyl acrylate, isooctyl acrylate, octadecyl acrylate, ethyl acrylate, amide, and imide. And / or, the composition of the substrate layer includes one or more of the following: polyolefin, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinyl chloride, polytetrafluoroethylene, polyacrylonitrile, polymethyl methacrylate, polyimide, polyetheretherketone, polyethylene terephthalate, polybutylene terephthalate, poly(p-phenylene terephthalamide), poly(m-phenylene isophthalamide), cellulose, polyurethane, poly(p-phenylenebenzodiazole), polyetherimide, polyphenylene sulfide, or copolymer systems derived from the above polymers.

8. The battery according to claim 6, wherein, The heat-resistant layer comprises a third particle and a first binder. The third particle is composed of one or more of the following: boehmite, alumina, barium sulfate, magnesium oxide, magnesium hydroxide, silicon dioxide, tin dioxide, titanium dioxide, calcium oxide, zinc oxide, zirconium oxide, yttrium oxide, nickel oxide, cerium oxide, zirconium titanate, barium titanate, magnesium fluoride, melamine cyanurate, 4,6-dimethyl-2-phenylpyrimidine, uracil, cytosine, 2,4-dimercaptopyrimidine, 2,4-dimercapto-5,6-diaminopyrimidine, and lithium aluminum titanium phosphate. Preferably, the first adhesive comprises one or more of polyvinyl alcohol, styrene-butadiene rubber, ethylene-vinyl acetate copolymer, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polymethyl methacrylate, polybutyl methacrylate, styrene-acrylic latex, polyacrylonitrile, ethyl polyacrylate, polyvinyl acetate, polyacrylate, polyvinylidene fluoride polyurethane, polyvinylidene fluoride-hexafluoropropylene, or copolymer systems derived from the above polymers.

9. The battery according to claim 6, wherein, The thickness of the heat-resistant layer is 0.2μm-5μm; And / or, the thickness of the substrate layer is 3μm-12μm; And / or, the puncture strength of the diaphragm is 200gf-600gf.

10. The battery according to claim 1, wherein, The electrolyte includes lithium hexafluorophosphate, and the weight percentage of lithium hexafluorophosphate in the electrolyte is 12%-23%.